Prevalence of difficult intubation and failed intubation in a diverse obstetric community-based population. (2nd December 2017) - Pollard, Richard; Wagner, Matthew; Grichnik, Katherine; Clyne, Brittany C.; Habib, Ashraf S.
Abstract: Objective: To describe the incidence of difficult and failed intubations in obstetric patients during a 6 year period monitored by a quality assurance program together with American Society of Anesthesiologists Physical Status (ASA PS) scores, and obesity (body mass index >30 kg/m 2 ). Methods: Following Institutional Review Board approval, data about obstetric patients who experienced unanticipated difficult or failed intubations from 2010 to 2015 was obtained from the quality assurance database of a large, community-based anesthesiology group practice. The database employs standardized definitions for difficult intubation (>3 laryngoscopic attempts by experienced providers) and failed intubation (inability to intubate leading to surgical airway or waking up the patient). ASA PS scores and comorbidities were also identified for obstetric general anesthetics using an internally developed quality assurance program, Quantum Clinical Navigation System. Results: There were 2802 obstetric general anesthetics in the database of which 1085 (38.7%) were deemed as emergencies. There were no cases of failed intubation and seven cases of unanticipated difficult intubations (1:400 cases, 0.25% of all obstetric general anesthetics, 95% confidence interval 0.1–0.5%), six of which occurred during emergency surgery. There was an increase in obesity ( p = .003) and ASA PS ( p = .02) over the period of the study. The incidence of difficult intubation was not found to be significantly changed ( p = .68). Conclusions: Despite an increase in ASA PS score and obesity, there was no increase in the incidence of difficult intubation in obstetric patients. Limitations of the study include its retrospective design, and the small number of difficult intubation cases identified.